PENGARUH PERUBAHAN TINGGI HAK TERHADAP VOLUME KAKI DI HITUNG DARI SHOE LAST - Wawan Budi Setyawan (Politeknik ATK Yogyakarta, 2015)
Shoes is a footwear consisting of a sol, right, hood, strap, and tongue. High heels become one of the main attraction for women due to wearing high heels can support the appearance of a woman. High-heeled shoes have several sizes and shapes. A shoemaker should take into calculate the volume of the foot while making shoes. The higher the heel is used, then the assumption of the volume of the foot will change as well. How big is the change in the volume of the foot which in this case is represented by the shoe last as the coppier to change shoes high heels become into research questions. The author in this case chose the title